Pengaruh Catu Daya pada Kecepatan Motor Navigasi Mobile Robot Line Follower Berbasis Arduino Nano - Samsul Arifin; Siti Sendari; Ilham Ari Elbaith Zaeni (Universitas Ngeri Malang, 2021)
Mobile robot line follower is still a very popular research topic. Line follower robots are the basis for developing robot applications in various fields. The key to a robot's success is being able to read and follow lines precisely and quickly. Many control system methods have been developed to improve the robot's ability to follow the line. Several methods including PID and Fuzzy which have been widely studied. Even though it is supported by the control method there is one problem that affects the robot navigation system, namely the power supply voltage. The robot's power supply is usually sourced from a battery which within a certain usage period will decrease. When the power supply is reduced, the robot's navigation system will also have problems, whether it is getting slower or the robot becomes zig-zag. When the power supply voltage is fully charged, the DC motor will tend to be fast and conversely, when the power supply voltage drops, the DC motor will run slower. The results of testing the effect of the power supply voltage on the speed of robot navigation show that in the power supply range of 8.44V to 6V the best speed is obtained at a voltage of 7.2V. Mobile robot line follower masih menjadi topik penelitian yang sangat populer. Robot line follower menjadi basic untuk mengembangkan aplikasi robot dalam berbagai bidang. Kunci keberhasilan robot adalah dapat membaca dan mengikuti garis dengan tepat dan cepat. Metode sistem kontrol banyak dikembangkan untuk meningkatkan kemampuan robot dalam mengikuti garis. Beberapa metode diantaranya PID dan Fuzzy yang sudah banyak diteliti. Meskipun didukung oleh metode kontrol ada satu masalah yang berpengaruh pada sistem navigasi robot yaitu tegangan catu daya. Catu daya robot biasanya bersumber dari baterai yang dalam jangka waktu pemakaian tertentu akan berkurang. Pada saat catu daya berkurang maka sistem navigasi robot juga akan bermasalah baik itu semakin melambat atau robot menjadi zigzag. Pada saat tegangan catu daya terisi penuh maka motor DC akan cenderung kencang dan sebaliknya ketika turun tegangan catu dayanya maka motor DC akan lebih pelan. Hasil pengujian pengaruh tegangan catu daya pada kecepatan navigasi robot menunjukkan bahwa pada range catu daya 8,44V sampai 6V didapatkan kecepatan terbaik berada pada tegangan 7,2V.